2013
DOI: 10.1155/2013/684739
|View full text |Cite
|
Sign up to set email alerts
|

Tidal Influence on Nutrients Status and Phytoplankton Population of Okpoka Creek, Upper Bonny Estuary, Nigeria

Abstract: Okpoka Creek of the Upper Bonny Estuary in the Niger Delta is a tidal creek receiving organic anthropogenic effluents from its environs. The study investigated the influence of tides (low and high) on the species composition, diversity, abundance, and distribution of phytoplankton. The surface water and phytoplankton samples were collected monthly from May 2004 to April 2006 at both tides from ten stations according to standard methods. Phytoplankton was identified microscopically. Species diversity was calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 15 publications
5
16
1
Order By: Relevance
“…Dinoflagellates abundance, especially the orders Prorocentrales and Gonyaulacales, was low in disturbed station contrary to diatoms that were more abundant. Phytoplankton variation between control and disturbed conditions is similar to those found by Ben Brahim et al [19] in the south of Tunisia (Gulf of Gabes), by Wang et al [20] in Baiyangdian Lake (China), and by Davies and Ugwumba [21] in Okpoka Creek (Nigeria). In addition, some fertilization experiments have shown shifts in relative dominance among algal species, with a shift towards cyanobacteria [2] and diatoms [22] under nutrient enrichment.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Dinoflagellates abundance, especially the orders Prorocentrales and Gonyaulacales, was low in disturbed station contrary to diatoms that were more abundant. Phytoplankton variation between control and disturbed conditions is similar to those found by Ben Brahim et al [19] in the south of Tunisia (Gulf of Gabes), by Wang et al [20] in Baiyangdian Lake (China), and by Davies and Ugwumba [21] in Okpoka Creek (Nigeria). In addition, some fertilization experiments have shown shifts in relative dominance among algal species, with a shift towards cyanobacteria [2] and diatoms [22] under nutrient enrichment.…”
Section: Discussionsupporting
confidence: 86%
“…The same observation was made in Lebanese coastal waters [25]. Indeed, Egge and Aksnes [26] and Fouillaron et al [27] showed that diatoms always numerically dominated the phytoplankton community when silicic acid (DSi) concentrations were above 2 M. Previous studies have shown that nutrient enrichment was associated with changes in species composition [1,21,28]. However, each microalgal group displayed a unique spatial pattern in response to N and P enrichment [2].…”
Section: Discussionmentioning
confidence: 54%
“…In a tideinfluenced Okpoka Creek of Upper Bony Estuary Nigeria, higher concentrations of nitrate, phosphate, and sulfate were found at low tide than at high tide. Similarly, higher density of chrysophytes and euglenoids was observed at low tide than at high tide (Davis and Ugwumba 2013). It is likely that such tide-induced changes in nutrient and phytoplankton composition have also occurred in few of our stations (e.g., OC1, OC2, CS4) where tidal influence is more prominent.…”
Section: Spatiotemporal Variation In Physicochemical Parametersmentioning
confidence: 58%
“…Diatoms are valuable indicators of ecological quality as they respond directly and sensitively to many physical, chemical and biological changes in aquatic environment and may quickly respond to changing physical, chemical, and biological conditions in the environment [23,24]. The physicochemical parameters such as temperature, irradiance, salinity and nutrients were found to influence the occurrence of diatoms.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of Guinardia delicatula, Skelletonema costatum, Climacosphena moniligera, Striatella unipunctata and Thalassiosira decipiens in the water column, is closely associated with the periods of increased mixing. These passive organisms were distributed throughout the water column during the increased shear at each tide [23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Discussionmentioning
confidence: 99%